Implementation of Instant Massaging & Presence Services in IP Multimedia Subsystems - Meenakshi (My University, 2007)
The IP Multi-Media Subsystem (IMS) is an IP multimedia and telephony core network. It is defined by 3GPP and 3GPP2 standards and organizations based on IETF Internet protocols. IMS is access independent. IMS permits and enhances real time, multimedia mobile services such as rich voice, video telephony, messaging, conferencing and push services by responding to the emerging trend to move toward a common, standardized subsystem. IMS represents a standardized, reusable platform providing a better way to experiment with, deploy, integrate, and expand consumer and enterprise voice and data services. The next generation networks provided a new face to the telecommunication world. Earlier the main emphasis was on speech and speech related services, but nowadays the main aim is to enable faster data rates and various multimedia services. IP Multimedia Subsystems (IMS) provide a single platform for all the present as well as future technologies. IMS enables a whole new set of services such as instant messaging & presence services which is a novel concept of IMPS (Instant Messaging and Presence Service) brings instant messaging, one of the most rapidly growing Internet services, to mobile networks. IMPS provide several advantages over conventional SMS messaging, including group messaging, presence information and conversations. IMPS is not limited to the mobile environment - it can provide a global service spanning both fixed and mobile subscribers. It includes client device availability (my phone is on/off, in a call), user status (available, unavailable, in a meeting), location, client device capabilities (voice, text, GPRS, multimedia) and searchable personal statuses such as mood (happy, angry) and hobbies (football, fishing, computing, dancing). Since presence information is personal, it is only made available according to the user's wishes - access control features put the control of the user presence information in the users' hands. Instant Messaging (IM) is a familiar concept in both the mobile and desktop worlds. Desktop IM clients, two-way SMS and two-way paging are all forms of Instant Messaging.
Keywords: IP Multimedia Subsystems; Instant Massaging; Session Initiation Protocol; Proxy Server